Total phenolic content and antioxidant activity of wild anise foliage (Piper auritum Kunth) and its nutraceutical effect for pigs in post-weaning - Caicedo, Willan (2020)
The content of phenolic compounds and antioxidant activity in powder and cooked extract of wild anise foliage (Piper auritum Kunth) and its effect as a phytobiotic additive for pigs in the post weaning phase were evaluated. Fresh wild anise plants were collected and processed in the laboratory to obtain the powder and foliage extract. The total phenolic content (Folin-Ciocalteu method) and antioxidant activity (ABTS method) were determined. Thirty castrated piglets Landrace x Duroc of 6 ± 0.2 kg were distributed in three experimental groups: T0 (Basal diet without antibiotic growth promoter) BDWAGP; T1 (BDWAGP + inclusion of 1 g of powder/100 g of feed) and T2 (BDWAGP + inclusion of 10 ml of extract/100 g of feed). Daily feed consumption (DFC), daily weight gain (DWG), feed conversion (FC), final weight (FW) and incidence of diarrhoea (ID). The powder and extract showed 7.92 mg gallic acid/g and 0.75 mg gallic acid/ml sample (total phenols) and 0.11 mg TROLOX/g and 0.12 mg TROLOX/ml sample (antioxidant activity), respectively. T2 pigs had better DFC, DWG, FC and FW (p<0.05). Pigs of T1 and T2 had a lower incidence of ID (p<0.05). Dietary supplementation with cooked extract of wild anise foliage in the diet of pigs during the post weaning phase improved feed consumption, feed conversion, bodyweight gain, final bodyweight and reduced the incidence of diarrhoea.